Oxford studies in metaphysics. - Bennett, Karen, 1971-; Zimmerman, Dean W. (Oxford Studies in Metaphysics., 2012)
'Oxford Studies in Metaphysics' is dedicated to the timely publication of new work in metaphysics, broadly construed. These volumes provide a forum for the best new work in this flourishing field. They offer a broad view of the subject, featuring not only the traditionally central topics such as existence, identity, modality, time, and causation, but also the rich clusters of metaphysical questions in neighbouring fields, such as philosophy of mind and philosophy of science.